Metagenomic Analysis of Bacterial Communities in the Musi River Estuary, South Sumatra, Indonesia - Melki; Mustopa, Apon Zaenal; Meiyerani, Jeni; Ramadhian, M. Zalfa; Purwiyanto, Anna Ida Sunaryo; Putri, Wike Ayu Eka; Hartoni (HAYATI Journal of Biosciences, 2025)
Understanding the diversity, function, and ecological dynamics of bacterial communities depends on unique transitional environments, estuaries. Knowledge on bacterial taxa in the Musi River estuary, South Sumatra still eludes, however. This effort aims to identify bacterial species in estuary waters using metagenomic analysis based on 16S rRNA gene. Surface water samples from three study locations were analysed by DNA isolation, nanodrop spectrophotometer qualitative assessment, 16S rRNA gene amplification, electrophoresis, and Illumina NovaSeq sequencing. Results showed that Proteobacteria predominated at all sites, followed by Campilobacterota, Cyanobacteria, and Bacteroidota. At the class level, Gammaproteobacteria was most common, followed by Alphaproteobacteria and Campylobacteria. Dominant bacterial orders were Campylobacterales, Rhodobacterales, and Pseudomonadales while the most common families were Arcobacteraceae, Rhodobacteraceae, and Pseudomonadaceae. The most plentiful genera were Rheinheimera, Pseudomonas, and Pseudarcobacter. Variations in bacterial spread among stations suggest environmental factors including salinity, nutrient availability, and human activities influencing microbial community composition. Ternary plots, heat maps, and krona diagrams were employed to disclose distinct patterns of bacterial community dispersion in the estuary. This paper underscores the importance of metagenomic research in illuminating microbial diversity in estuarine environments and its impact on ecological dynamics and water quality.